Preparation of photocurable silica-titania hybrid coatings by an anhydrous sol-gel process - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (SPRINGER, 2011)
Photocurable silica-titania hybrid coatings were prepared through an anhydrous sol-gel process. Moreover, test samples were prepared by the addition of definite ratios of fluoro acrylate oligomers into the formulations to manage the optical properties of transmitted light. Formulations were applied to corona-treated polycarbonate substrates. Upon adding the inorganic component to the coating material, thermal, mechanical, and other properties, such as hardness, gloss, contact angle, and flame resistance were improved. The photocured hybrid films showed an increase in the refractive index with increasing the titanium tetraisopropoxide content. As expected, a decrease was observed in the refractive index of the coatings with the incorporation of fluoro acrylate resin. The surface morphology of the hybrid films was characterized by ESEM analysis. In addition the chemical composition of the surface of the coatings was identified by ESEM-EDS technique. ESEM studies indicated that inorganic particles were dispersed homogenously throughout the organic matrix.
Keywords: Refractive index; Organic-inorganic hybrid; UV-curable; Coating; ACRYLATE COATINGS; FILMS; NANOCOMPOSITES; BEHAVIOR